Giant expanded perivascular spaces: literature review and description of a clinical case - E. A. Gavrilova; V. A. Ott; A. A. Yakovlev; S. A. Yakovlev; A. G. Smochilin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2021)
The differentiation of giant perivascular spaces is the complicated task due to its rare occurrence and multiple differential series. Cystic neoplasms, parasitic cysts, and lacunar strokes are need to be excluded. Knowing and ability to recognize pathognomonic radiological features can help to prevent excessive diagnostics and make the correct diagnose quickly. The article presents a clinical case of a rare and difficulty diagnosing variant of giant perivascular spaces.